2006
DOI: 10.1080/14034940510032149
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Road traffic injuries in India: A review of the literature

Abstract: There is lack of population-based data on road traffic injuries in India and there is large heterogeneity in the published data. This is an important research agenda for the country. Immediate steps are required to curb this problem to limit the loss of life and resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
(28 reference statements)
4
26
0
1
Order By: Relevance
“…Deaths in this age-group are likely to cause substantial household deprivation from the loss of a key wage earner [25]. Our mortality rates are consistent with the results of several local studies in India, including showing that a marked excess in young and middle aged males [26].…”
Section: Discussionsupporting
confidence: 80%
“…Deaths in this age-group are likely to cause substantial household deprivation from the loss of a key wage earner [25]. Our mortality rates are consistent with the results of several local studies in India, including showing that a marked excess in young and middle aged males [26].…”
Section: Discussionsupporting
confidence: 80%
“…A study in rural Haryana reported 8% prevalence of agriculture related injuries. 8 Prevalence of repeated injury is around eight percent. Occurrence of repeated injury suggests the persistent reckless behavior or persistence of risk element in the surrounding, which has significant policy implication as there is potential for possible initiative of risk reduction.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies were conducted to explore the injury epidemiology around the globe. [8][9][10] However extreme difficulty lies in relating the findings due to heterogeneity of measurement methods and statistical operations. The Pondicherry study that share relatively similar socio-demographic profile reported similar high prevalence for those 18 years and older and among men.…”
Section: Discussionmentioning
confidence: 99%
“…They are the most common cause of head injuries (64%) resulting in varying levels of disabilities and death of the victims before reaching a hospital. [2][3][4][5][6] RTAs are a significant burden on the health care system in India and the estimated out of pocket medical and related expenditure is reported to range between 10,518 to 10,905 INR.…”
Section: Introductionmentioning
confidence: 99%